FORMALIZATION ENVIRONMENTAL FACTORS ON THE ORGANIZATION OF RAIL TRANSPORT (Transport systems and technologies, 2018)
Article is devoted to the development of technical, technological, organizational and other factors to improve efficiency and quality of service for passengers and cargo. To improve system model railroading of the environmental factors that affect this system. Proposals for improving the system of rail transportation, the quality of service for passengers, cargo and improve the efficiency of rail transportation are given.
Keywords: rail transportation, quality of service for passengers and cargo, the organization of transportation, environmental factors